(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The article scientifically substantiates information about the spiritual heritage of Khoja Muhammad Porso, the great representative of the Naqshbandi tariqat in the Timurid period, his place in the spiritual life of Central Asia, his philosophical essence. During the Timurid period, the main attention was paid to the issue of describing Sufism, more precisely, the Khodjagon-Naqshbandi tariqat.